Strategic Responses to the Illegal Downloading of Music:A Qualitative Study - COOKE, George Matthew (2006)
This thesis focuses upon the illegal downloading of music; this topic represents a recent, fast-changing and under-explored area. Illegal downloading is amongst the most damaging phenomena experienced by the music industry today. It is described by Densmore (2002, p1), for example, as a critical threat to a traditionally stable business sector, and by Redmond (cited in Morris, 2005, p1) as a trend which could lead to the industry as a whole, going out of business. Most sources including the industry itself estimate losses as a consequence of illegal downloading at billions of dollars (e.g. BPI; RIAA). It is a technically illegal activity, which otherwise lawabiding people appear to have few qualms in partaking and despite the best efforts of individual firms, industries and even legal mandates to prevent it, it continues to grow. From this evidence it is apparent that there is an element of dissonance in attitudes between the music industry and those who illegally download. The aim of this thesis is to investigate and explore this dissonance, with a view to informing and identifying a more effective range of strategic responses to the illegal downloading problem.